Ukraine invasion and votes in favour of Russia in the UN General Assembly - Mohammad Reza Farzanegan; Hassan Gholipour Fereidouni (Philipps-University Marburg, School of Business and Economics, 2022)
Why did some countries vote not to condemn Russia's invasion of Ukraine at the United National General Assembly's first emergency session since 1997? Our study examines different economic, political, geographic and historical reasons behind the voting behaviour of several countries in favour of Russia. Probit regressions show that higher dependence on military exports from Russia, years ruled by leftists, access to Russian markets for exports, being a major recipient of Russian aid, being former members of Soviet Union and sharing borders with Russia are positively associated with the probability of voting in favour of Russia. Factors which reduce the probability of support for Russia over the Ukraine invasion are higher levels of civil and political freedom within a country and percentage of exports from Russia to partners in total Russia exports.
Keywords: 330; Internationale Organisation; Militärische Intervention; Russisch; Internationale Konferenz; Wahlverhalten; Strategische Allianz; Ukraine; Russland; Welt